The effects of preoperative non-invasive cardiac tests on delay to surgery and subsequent mortality in elderly patients with hip fracture - Mutlu, Harun; Bilgili, Fuat; Mutlu, Serhat; Karaman, Özgür; Çakal, Beytullah; Özkaya, Ufuk (IOS Press, 2016)
OBJECTIVE: To investigate the effects of preoperative cardiac tests on the surgical treatment plan and subsequent effects on mortality in elderly patients with hip fracture. METHODS: In this retrospective study, 116 patients aged 60 years or above who underwent hip fracture surgery between 2010-2013 were evaluated. Of the patients with similar preoperative clinical risk factors, 20 patients with additional preoperative cardiac tests such as echocardiography or thalium scintigraphy constituted Group 1, whereas 28 patients without additional cardiac tests constituted Group 2. Statistical analyses were performed using the SPSS 21 statistical package software. Normal distribution of the data was determined by the Shapiro-Wilk test and histography. Intergroup and mortality comparisons were performed by Mann-Whitney U, Yates-corrected chi-square and Fisher's exact tests. RESULTS: The mean time between fracture and operation was 6 days (range, 4-14) in Group 1, and 2 days (range, 0-3) in Group 2. There was a significant difference in time-to-operation between the groups (p < 0.001). The age and gender distribution of both groups were homomgenous (p = 0.64, p = 1.0). Both groups were comparable in terms of fracture type, treatment, and anesthesia (p = 0.36, p = 0.42, p = 1.0). At the end of 1 year, six (30%) patients in Group 1 and three (10.7%) patients in Group 2 were deceased. Both groups were comparable in terms of mortality (p = 0.137). There was a significant difference between the two groups in terms of complications (p < 0.05). CONCLUSIONS: Unnecessary cardiac tests in elderly patients with hip fracture led to a delay in their surgery, yet did not change their cardiac treatment plan. This delay in obtaining hip fracture surgery increases complication rates, hospitalization duration, and costs.
WOS: 000370181500007
PubMed ID: 25881693
Keywords: Cardiac Tests; Hip Fracture; Mortality